Management of Farm Development and Their Role in the Socio-Economic Recovery of Rural Areas - Oleksandr Shpykuliak; Mariana Humeniuk; Diana Shelenko; Dmytro Nemish; Sergiy Balaniuk (Journal of Vasyl Stefanyk Precarpathian National University)
Farms in the conditions of wartime uncertainty have been distinguished by their flexibility and ability to adapt to changing economic conditions in Ukraine, high maneuverability in relation to changing market conditions, and mobility and dynamism in terms of the possibility of their transformation, winding down and relocation of production. Farming, in which the capabilities of the family and the farm are harmoniously combined in the development of economic, environmental, social and cultural functions, has the greatest opportunities in ensuring the sustainable development of rural areas, as well as achieving resilience criteria, which makes the study of its development relevant. The purpose of the study is to determine the trends in the development of farms in Ukraine in the conditions of uncertainty caused by martial law and to substantiate measures to ensure their sustainable development. The generalization of scientific research made it possible to systematize the classification of farms by the criterion of agricultural land area and nature of activity. It was established that from the point of view of compliance with the principles of sustainable development, it is advisable to distinguish such promising types of farming as craft, organic, social, veteran and solidarity. The functions of farms in the post-war reconstruction of rural areas are substantiated.According to the results of the assessment of the current state and development of farms in Ukraine, it was determined that the average area of one farm is 187 hectares, and the share of farms occupying an area of up to 100 hectares is 68.9% of the total number of farms. The largest group in terms of number (31.9%) is the group of farms with an area of 20-50 hectares. As a result of the negative impact of a number of factors caused by martial law, the value of the gross output of farms in Ukraine decreased by 4.5% in dynamics, in particular the value of the gross output of crop production - by 4.3%. The value of the gross output of livestock production fluctuates at the level of 6-7 billion UAH. with a slight adjustment for uncertainty conditions.For the development of farms on the basis of sustainability, a set of measures is proposed based on stimulating innovative, social and institutional functionality.